Learning the trade of navigating and tinkering within a disparate welfare system : Older adults as bricoleurs of home arrangements and support - Möllergren, Glenn; Jönson, Håkan ; 0000-0003-2347-7656; Granbom, Marianne ; 0000-0001-7456-2039 (Health & Place, 2025)
Challenging conventional provider-oriented perspectives on older adults' spatial realities, this study explores how community-dwelling care users in Sweden manage their home environments. It investigates how older adults use the welfare system and coordinate widely available but disparate material and social resources to achieve a spatially sustainable ageing-in-place. Research on domiciliary care for older adults has largely focused on the provider, overlooking the skills and strategies older care users themselves employ to make arrangements work; this study adopts a fresh lens by examining the active engagement of older adults in shaping their own home arrangements. The data comprised twelve qualitative interviews with older care users, along with walk-alongs in their homes, focusing on how different areas of the home were used in everyday life. The concepts of bricoleur, bricolage, and tinkering, were employed to analyse the activities and arrangements respondents implemented to utilise services in managing their daily lives. The findings revealed that participants had been prompted to develop sophisticated procedures and competencies, leveraging supportive networks and combining housing adaptations, assistive devices, and innovative uses of household items to make the services useful. The study highlights the importance of recognising the active coordination efforts of older care users and underscores the need to focus on their expertise and adaptive learning within supportive systems. An eldercare provision such as the one in Sweden, offering a variety of different services, can be perceived as fragmented and challenging to navigate, necessitating a user-centred approach to improve accessibility and effectiveness.
Copyright © 2025 The Authors. Published by Elsevier Ltd.. All rights reserved.